El Manual de Don Alfonso cuarenta Cursos después - Ibán Pérez, Iván C. (Cuadernos de Historia del Derecho, 2011)
Personal digression of the author as a result of the re-reading of the 1971 García-Gallo’s course textbook, forty years after having faced the same Manual as a student. The author examines the sources and authors used by professor García-Gallo, as well as his theories and inclinations over the historical evolution of our law, before reaching the conclusion that legal historians nor the jurists do not know what the law is.